Aklimatisasi Anggrek (Phalaepnopsis amabilis) dengan Media Tanam yang Berbeda dan Pemberian Pupuk Daun - Wukir Tini, Etik; Sulistyanto, Prasmaji; Sumartono, Gregorius Hadi (Jurnal Hortikultura Indonesia, 2019)
The purpose of the research is to find the most appropriate planting medium and the concentration of leaf fertilizer for acclimatization of Phalaenopsis orchids in order to increase the plant growth. The research was conducted from November 2017 to June 2018 in the screen house. The design was laid in Randomized Completed Block Design with two treatment factors, the first one is the plant medium (fern, cocofiber, and kadaka root) and the second one is the concentration of leaf fertilizer (without fertilizer, 1 g L-1, 2 g L-1, 3 g L-1 of leaf fertilizer). The results showed that kadaka roots could increase the leaf area growth by 19.2% compared to ferns and 26.67% compared to coconut fiber. Leaf fertilizer concentration of 2 g L-1 is the best concentration that can increase in leaf area addition by 78.31% and the amount of chlorophyll by 25.58%. The combination of plant substrate types and fertilizer concentration have not increased the growth of Phalaenopsis orchid plants in the acclimatization phase.Keywords: coconut fiber, concentration, fern, plant growth, kadaka root